2018
DOI: 10.1161/circep.117.006091
|View full text |Cite|
|
Sign up to set email alerts
|

Right Ventricular Dysfunction and Long-Term Risk of Sudden Cardiac Death in Patients With and Without Severe Left Ventricular Dysfunction

Abstract: Presence of RVD in patients with a history of preexisting cardiac disease is an independent predictor of SCD irrespective of left ventricular ejection fraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 44 publications
0
21
0
Order By: Relevance
“…Risum et al 23 found that RV free-wall strain as measured by 2-dimensional echocardiographic analysis was significantly associated with ventricular arrhythmias/SCD and superior as a predictor compared to TAPSE in an acute myocardial infarction population. In one of the largest studies to date of 5463 subjects who all had been admitted to the coronary care unit at Mayo Clinic, Rochester, Minnesota, Naksuk et al 24 found that moderate to severe RV dysfunction as determined jointly by TAPSE, RV index of myocardial performance, and tricuspid annular S 0 wave velocity was an incremental predictor of SCD in both patients with LVEF 35% and those with LVEF .35%. These studies all indicate that RV dysfunction by various means of assessment can be predictive of SCD risk.…”
Section: Discussionmentioning
confidence: 99%
“…Risum et al 23 found that RV free-wall strain as measured by 2-dimensional echocardiographic analysis was significantly associated with ventricular arrhythmias/SCD and superior as a predictor compared to TAPSE in an acute myocardial infarction population. In one of the largest studies to date of 5463 subjects who all had been admitted to the coronary care unit at Mayo Clinic, Rochester, Minnesota, Naksuk et al 24 found that moderate to severe RV dysfunction as determined jointly by TAPSE, RV index of myocardial performance, and tricuspid annular S 0 wave velocity was an incremental predictor of SCD in both patients with LVEF 35% and those with LVEF .35%. These studies all indicate that RV dysfunction by various means of assessment can be predictive of SCD risk.…”
Section: Discussionmentioning
confidence: 99%
“…Right ventricular dysfunction, detected by echocardiogram, with or without concomitant left ventricular dysfunction is a long‐term risk for SCD . The presence of moderate to severe right ventricular dysfunction doubles the hazard of SCD …”
Section: Functional Abnormalitiesmentioning
confidence: 99%
“…19 The presence of moderate to severe right ventricular dysfunction doubles the hazard of SCD. 20 In summary, left ventricular ejection fraction is the most widely used prognostic marker to predict sudden cardiac death and is also the primary marker for formulating therapeutic strategies. However, other echocardiographically derived determinants of structural and functional abnormalities beyond LV EF are important in risk stratification for sudden cardiac death.…”
Section: Fun C Tional Ab Normalitie Smentioning
confidence: 99%
“…Importantly, new insights show that although the RV consists of, at first glance, the same cardiomyocytes as the LV, it is in fact derived from a different set of precursor cells, with complex three-dimensional anatomy and a very distinct contraction pattern [8]. Recent studies further sparked this renewed interest, showing that RV function is an important predictor of survival in patients with heart failure (HF), PAH, and CHD [9][10][11]. Nevertheless, profound knowledge of normal loading conditions and physiological adaptations ensuing morphology of the RV remains limited [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%